High intensity focussed ultrasound treatment planning for renal tumour ablation - Abbas, MA (2019)
The use of High Intensity Focussed Ultrasound for the thermal ablation of renal tumours provides a completely non-invasive method for treatment, which is advantageous for patients who are not eligible for surgery due to co-morbidity issues. However, clinical trials have shown variable results with challenges to the delivery of the ultrasound beam related to the intervening tissue layers. The use of patient-speciﬁc models is investigated as a means to provide a treatment planning step to aid clinicians in the choice of the transducer’s position and ultrasound power for the treatment.